Total-body toning - Dale, Lashaun; Fink, Doug.; Human Kinetics (Organization). (Champaign, IL : Human Kinetics, 2010)
Offers specific workouts to those who want to shape and sculpt their bodies or specific body regions, improve endurance, increase fitness levels, or lose weight. Eight 10-minute segments provide intervals of cardio and strength training to give viewers more focused workouts and better results.
Author, Lashaun Dale ; director, Doug Fink.
Host : Lashaun Dale.
DVD format.
Region code'universal'.
Keywords: Exercise; Physical fitness